Analyse des invitations de chercheurs étrangers par l'EHESS - Wiebke Keim (Les éditions de la Maison des sciences de l'Homme, 2010)
This article presents an empirical analysis of the unequal international division of labour within the social sciences, noticeable in the forms of exchange and communication between researchers of Northern and Southern countries. After a brief review of current literature, empirical data concerning the practice of inviting foreign researchers to the École des Hautes Études en Sciences Sociales (EHESS) in Paris are analysed. The article shows in how far the areas of competency for which researchers are invited, limits those coming from the continents of the South to presenting, in their majority, local themes, while their colleagues affiliated to north-Atlantic institutions contribute more considerably to general theory-building.